Production of amour plate by compaction inter-layered powder press surpasses 3000 tonne - Mohd Asyraaf Norazmi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
With modernity outstanding of technoligy infrastructure and technology infrastructure and highly capable by first world countries they are able to produce armour plates with the highest quality. Malaysia there still lack in heavy duty press technology that able to compact the metal powder by compressing ability reach 160,000 tonne as there available in the modern countries. Logically this techonology will lead the higher cost of manufacturing due to it requires the use of higher consumption energy of production and expertise in handling the process making of it.